Structural model updating using adaptive multi-response Gaussian process meta-modeling. (15th January 2021) - Zhou, K.; Tang, J.
Highlights: Multi-response Gaussian process (MRGP) emulation is formulated for model updating. Adaptive sampling strategy is established to guide the search of unknown parameters. MRGP meta-model is iteratively refined throughout searching. Case studies demonstrate the high efficiency and accuracy of the new framework. Abstract: Finite element model updating utilizing frequency response functions as inputs is an important procedure in structural analysis, design and control. This paper presents a highly efficient framework that is built upon Gaussian process emulation to inversely identify model parameters through sampling. In particular, a multi-response Gaussian process (MRGP) meta-modeling approach is formulated that can accurately construct the error response surface, i.e., the discrepancies between the frequency response predictions and actual measurement. In order to reduce the computational cost of repeated finite element simulations, an adaptive sampling strategy is established, where the search of unknown parameters is guided by the response surface features. Meanwhile, the information of previously sampled model parameters and the corresponding errors is utilized as additional training data to refine the MRGP meta-model. Two stochastic optimization techniques, i.e., particle swarm and simulated annealing, are employed to train the MRGP meta-model for comparison. Systematic case studies are conducted to examine the accuracy and robustness of the new framework of model updating.